KONSEKUENSI PENERAPAN TEORI KOMUNIKASI DALAM KEGIATAN PEMBELAJARAN TATAP MUKA - Waluyo Adi (MAJALAH ILMIAH PEMBELAJARAN, 2008)
Communication theory is very helpful in the success of face-to-j(1celearning activity. Therefore, the consequences of this theory to meet theentire requirement must be accomplishedMain component of this theory are communicator (educator),communication (student), context (learning environment), n;r ssage(learning material) and delivery system (methods and media).Educators are the most significant component, as they are required tohave the ability and the trust from students. This is naiVe if educators arenot able to pack learning material attractively and choose the mostappropriate media and methods. Moreover, learning environment has lobe able to give comfort, safety, fun and challenge.